1984
DOI: 10.1182/blood.v64.1.38.38
|View full text |Cite
|
Sign up to set email alerts
|

Intensified therapy in acute lymphoblastic and acute undifferentiated leukemia in adults

Abstract: One hundred seventy adult patients with acute lymphoblastic leukemia (ALL) or acute undifferentiated leukemia (AUL) were entered into a prospective multicenter therapy trial at 25 hospitals. The aim of the trial was to improve remission duration by using a modified form of an intensified induction regimen that was successful in childhood ALL, to define immunologic subtypes of ALL by use of cell-surface markers, and to extract other possible prognostic factors. The overall complete remission rate was 77.8%. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
7

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(23 citation statements)
references
References 40 publications
0
16
0
7
Order By: Relevance
“…CD56 was positive in three patients with AML, and these patients also expressed CD7. Treatment protocols consisted of intermediate dose Ara‐C and daunorubicine in patients with AML and protocol for German Multicentre Study Group for Adult ALL (GMALL‐1988) and intensive induction, consolidation and maintenance chemotherapy in patients with ALL (14–16). CR was achieved in nine patients (41%) (five ALL and four AML).…”
Section: Resultsmentioning
confidence: 99%
“…CD56 was positive in three patients with AML, and these patients also expressed CD7. Treatment protocols consisted of intermediate dose Ara‐C and daunorubicine in patients with AML and protocol for German Multicentre Study Group for Adult ALL (GMALL‐1988) and intensive induction, consolidation and maintenance chemotherapy in patients with ALL (14–16). CR was achieved in nine patients (41%) (five ALL and four AML).…”
Section: Resultsmentioning
confidence: 99%
“…Achievement of complete remission within 4 weeks of therapy has been a time‐honoured prognostic factor for adult patients with ALL (Hoelzer et al , 1984) (Table IV). In a report from the German multicentre study for the treatment of ALL, late achievement of CR was found to be the strongest adverse prognostic factor (Hoelzer et al , 1984). Based on this widely accepted concept, time to complete remission was used as initial stratification into risk groups in the MRC UKALL XII/ECOG E2993 study.…”
Section: Prognostic Factors Based On Responsementioning
confidence: 99%
“…The second and third generation schemes such as Macop-B, 7 Promace-CYTAbom 8 and the BFM-83 high-risk protocol 9 were used for high grade groups. CHOP, 10 BACOP 10 and MVPP 11 were used for intermediate groups. For low grade lymphoma, COP 11 and MVPP 11 were the most often used protocols.…”
Section: • Karin Zattar Cecyn • José Salvador Rodrigues De Oliveira •mentioning
confidence: 99%
“…CHOP, 10 BACOP 10 and MVPP 11 were used for intermediate groups. For low grade lymphoma, COP 11 and MVPP 11 were the most often used protocols.…”
Section: • Karin Zattar Cecyn • José Salvador Rodrigues De Oliveira •mentioning
confidence: 99%